2011
DOI: 10.1007/s00262-011-1049-8
|View full text |Cite
|
Sign up to set email alerts
|

Pilot trial of interleukin-2 and zoledronic acid to augment γδ T cells as treatment for patients with refractory renal cell carcinoma

Abstract: Prior to the advent of VEGF-targeted therapies, renal cell carcinoma (RCC) was among the few solid tumors shown to respond to cytokine-based therapies such as interleukin-2 (IL-2) and interferon alpha. Previous work has shown that aminobisphosphonates, including zoledronic acid (ZA), are capable of activating human Vγ9 Vδ2 T cells in vitro, and these cells can be further expanded with IL-2. Moreover, these Vγ9 Vδ2 T cells have cytolytic activity in vitro to multiple human tumor cell lines. In the current repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(96 citation statements)
references
References 36 publications
(41 reference statements)
1
95
0
Order By: Relevance
“…In particular, N-PBs that induce IPP accumulation, have been used in different clinical trials. [21][22][23][24] In this paper, we show that (i) the N-BP Zol, besides sensitizing CRC cells to gd T cell-mediated cytotoxicity, stimulates the expansion of Vd2 T cells with EM phenotype and antitumor cytotoxic activity; (ii) this effect is partially related to BTN3A1 expression and in particular by its cellular re-distribution; (iii) BTN3A1 is detected at the tumor site, both on epithelial and stromal cells, in the areas infiltrated by Vd2 T lymphocytes; (iv) Zol is effective in stimulating antitumor effector Vd2 T cells from ex-vivo CRC cell suspensions; and (v) both CRC cells and TAF can be primed by Zol to trigger Vd2 T cells. First, we found that different CRC cell lines exposed to Zol as a source of IPP, could successfully promote the expansion of gd T lymphocytes able to kill both the stimulating tumor cells and other CRC cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, N-PBs that induce IPP accumulation, have been used in different clinical trials. [21][22][23][24] In this paper, we show that (i) the N-BP Zol, besides sensitizing CRC cells to gd T cell-mediated cytotoxicity, stimulates the expansion of Vd2 T cells with EM phenotype and antitumor cytotoxic activity; (ii) this effect is partially related to BTN3A1 expression and in particular by its cellular re-distribution; (iii) BTN3A1 is detected at the tumor site, both on epithelial and stromal cells, in the areas infiltrated by Vd2 T lymphocytes; (iv) Zol is effective in stimulating antitumor effector Vd2 T cells from ex-vivo CRC cell suspensions; and (v) both CRC cells and TAF can be primed by Zol to trigger Vd2 T cells. First, we found that different CRC cell lines exposed to Zol as a source of IPP, could successfully promote the expansion of gd T lymphocytes able to kill both the stimulating tumor cells and other CRC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19][20] For this reason, different N-BPs have been used in anticancer clinical trials. [21][22][23][24] In the last years, the butyrophilin 3A (BTN3A, CD277) family, structurally related to B7 co-stimulatory molecules, has emerged as important structure contributing to Vg9Vd2 T cell stimulation. 25,26 This family in humans is composed of three isoforms: BTN3A1, BTN3A2 and BTN3A3, characterized by two extracellular immunoglobulin domains, a transmembrane region and all, but BTN3A2, by a intracellular signaling domain, named B30.2.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a pilot study on the effects of zoledronate and IL-2 was conducted in the United States by Malkovsky's group in 12 patients with metastatic renal cell carcinoma. 34 This trial sought to determine whether activation of the patients' TCRVc9Vd2 1 lymphocytes improved clinical outcomes. For six patients, the regimen consisted of three successive weekly cycles of intravenous injections of zoledronate (4 mg, day 1) with IL-2 (7 million IU/m 2 /day, from day 1 to day 5).…”
Section: Rationale For Harnessing CD Cells In Cancer Immunotherapymentioning
confidence: 99%
“…The γδ T cell based therapy is safe generally, however, the higher doses of stimuli co-injected with IL-2 increase the level of γδ cell expansion and the frequency of drug-related toxicity including thrombophlebitis, thrombosis, hyperglycemia, hypocalcemia, chest and musculoskeletal pain, gastritis, myocardial infarction and renal creatinine toxicity. In human, the maximum tolerable doses for BrHPP and zoledronate while administering along with IL2 are 1500 and 4 mg/m2 (every 28 days), respectively (Wilhelm et al, 2003;Dieli et al, 2003;Lang et al, 2011;Naoe et al, 2010;Kobayashi et al, 2007;Kobayashi et al, 2011;Kondo et al, 2008;Abe et al, 2009;Fournie et al, 2013).…”
Section: Gamma Delta T Cell Therapymentioning
confidence: 99%